Thermal dependency of microbial self-healing of concrete: Comparing the effectiveness of Bacillus strains at different temperatures, from room temperature to below zero - Seleem S.E. Ahmad; Mahmoud A. Elshazly; Ahmed A. Elakhras; Ahmed A. Elshami; Mohamed A.R. Elmahdy; Attitou Aboubakr (Case Studies in Construction Materials)
Demand for sustainable infrastructure has spurred the development of innovations, including bacterial self-healing concrete, which repairs cracks using Microbially Induced Calcite Precipitation (MICP). Examining the material's self-repair relative to bacterial concentrations (0 %, 1 %, 2.5 %), and strains (Bacillus Megaterium and Bacillus Sphaericus), performance was tested at 24°C and sub-zero temperatures (-16 ± 2 °C and −24 °C). Energy-dispersive spectroscopy, scanning electron microscopy, and X-ray diffraction were among the tests used; ultrasonic, compressive, and flexural testing were also employed. With compressive strength growing by 40.24 % after 28 days at normal temperature, Bacillus Megaterium (BM) showed notably better mechanical stability and crack-healing efficiency than Bacillus Sphaericus (BS) at sub-zero temperatures. At 0°C with a 2.5 % concentration, both strains attained 100 % crack healing. At low temperatures, BM raised compressive strength by 23.52 % while BS showed a drop. Whereas BS's modest 4.8 % gain at −16°C, BM's cold tolerance produced a strength rise of 54.87 % at 0°C.